MORF1 regulates the editing of orf224 transcript to modulate fertility in the polima cytoplasmic male sterility system of Brassica napus L. - Benqi Wang; Lei Chu; Huadong Wang; Jian Guo; Zunaira Farooq; Chaozhi Ma; Jingxin Tu; Jinxiong Shen; Jing Wen; Tingdong Fu; Bin Yi (Crop Journal)
The Brassica polima cytoplasmic male sterility (pol CMS) line causes complete and stable sterility and is most extensively used in breeding. The regulatory pathway, however, is not clear. In this work, we studied molecular interaction among several key genes involved in pol CMS. Firstly, we found that the multicellular organelle RNA-editing factor protein (Bna.MORF1) interacted with the pol CMS-restorer protein RFP using the yeast two-hybrid system. Secondly, knock down of Bna.MORF1 using CRISPR/Cas9 editing resulted in sterile transgenic lines. The function of the pol CMS sterility gene orf224 was further confirmed by ectopic expression of the gene in both Arabidopsis and Brassica. Furthermore, using CRISPR/Cas9 we determined that an anther-specific proline-rich protein (APG) was also involved in sterility. We propose a working model for pol CMS in Brassica napus that may expedite the utilization of this popular CMS line in Brassica breeding.